An Exploration of the Causes of the Failure of PPR Payments in the Wirogunan Residence Community during the Pandemic - Lailatul Mukaroma; Novi Puspitasari; Abdul Fatah (Optima Science, 2023)
his research aims to explore the causes of the failure of the Wirogunan Residence community's Home Ownership Financing payments during the pandemic and how the actions taken by the Wirogunan Residence community in overcoming problematic financing during the pandemic. This research uses a qualitative method with a case study approach and uses data collection techniques in the form of interviews. The results of the interviews suggested that during the pandemic, people who work as entrepreneurs experienced a decrease in income due to decreased consumer buying interest during the pandemic and some private employees at industrial factories experienced layoffs due to the work from home policy which made them lose income. The significant decline in income during the pandemic has an impact on PPR installment payments, resulting in delays to delinquent payments. To overcome the problem of PPR installment financing, the Wirogunan Residence community takes several actions by looking for additional income such as opening a business that is still needed during the pandemic, making loans to relatives or closest relatives to applying for financing restructuring at the bank.